FEATURE,NILAI, KEPUASAN DAN LOYALITAS PELANGAN - Hatta, Iha Haryani (Economic Faculty, Attahiriyah Islamic University, 2017)
The aim of this study was to determine the relationship of the features of the value, satisfaction, and customer loyalty; the effect on the value of customer satisfaction and loyalty; influence of satisfaction on customer loyalty. A total of 200 merchant PT. BANK XYZ as respondents was selected randomly. Analyses were performed using structural equation modeling (SEM). The analysis showed that the feature has a significant influence on customer value, but not for customer satisfaction and loyalty. The values has a significant influence on satisfaction, but not on customer loyalty. Satisfaction has a significant influence on customer loyalty. Discussion and conclusions described in the article. Keywords: features of the value, satisfaction, customer loyalty